A Bibliometric Analysis of the Link between Start-Up and Business Performance - Alexandru PARU; Cristian MARCU; Paul MARINESCU (Communications of International Proceedings, 2021)
The objective of this article is to present a bibliometric analysis by exclusively using the Web of Science database to determine the research areas with the greatest concentrations on the correlation analysis of two basic concepts for global economic progress: "start-up" and "business performance". The analysis has clearly and unequivocally shown that this interconnection of elements is on the upward trend in the interest of researchers over the last 10 years, with an accelerated course over the last 4 years. The main areas of development are the European Union, the United States of America and the United Kingdom, English being the main publication language for this works. However, the heterogeneity of studies and research is noted, which makes it necessary to develop cumulative studies and innovative references within a conceptual reference framework. In terms of research limitations, these may be derived from the fact that the analysis has included a single international database from which the reference works on the correlation between "start-up" and "business performance" may be lacking.
Keywords: Bibliometric analysis; start-up; business performance; business sustainability; entrepreneurship